Evaluation of Potting Mixtures for Raising Dalbergia sissoo Seedlings under Root Trainer System - Ginwal, H. S.; Rawat, P. S.; Bhandari, A. S.; Krishnan, C.; Shukla, P. K. (Indian Forester, 2002)
Experiments were conducted to standardize appropriate potting medium for raising Dalbergia sissoo seedlings under root trainer seedling production system. In two different experiments , two kinds of potting media were tried , one with various combinations of sand , soil and compost and the other with charcoal , rice husk and compost. A multivariate approach was adopted considering the seedling quality parameters i.e. sturdiness , root shoot ratio , ratio of fibrous/total root biomass , Dickson quality index , and root surface area , apart from the various growth and biomass traits of 3 month nursery growth. Dalbergia sissoo being a versatile and primary coloniser in riverine concession , came up very well in sand and compost combination (20% sand + 80% compost). However , it also performed well in other combinations of sand , soil and compost in the ratio of 1:1:3 ,1:0:4 and pure compost alone. In respect to the organic ingredients , combinations of charcoal , compost and rice husk in the ratio of 1:3:1 and 1:4:0 appeared satisfactory. Comparing the performance of both the types of potting media , it came to the notice that the sand , soil and compost combinations are fairly better for raising D. sissoo than the charcoal , rice husk and compost. The seedlings achieved significantly better growth , biomass and quality parameters when raised in sand , soil and compost than when raised in the potting mixture containing charcoal and rice husk. For the species like Dalbergia sissoo which is known to be a species of sandy alluvium soil , the ingredients like sand , soil and compost should be encouraged in the potting medium for raising in nursery.